PENURUNAN NOISE FIGURE PERFORMANCE (FN) PADA HETEROJUNCTION BIPOLAR TRANSISTOR SI/SI 1-X GEX BERDASARKAN PENGATURAN STRIPE EMITTER AREA (AE) DAN FRACTION MOLE (X) (Makara Journal of Science, 2010)
Reduction of Noise Figure (Fn) on Bipolar Heterojunction Si/Si1-x Gex based on Arrangements Stripe Emitter Area (Ae) and Mole Fraction (x). This paper investigates the influence of stripe emitter area (Ae) and fraction mole (x) concerning about noise figure performance (FN) at HBT SiGe. It takes the second generation of HBT SiGe IBM with Ae; 0.18 x 10 μm2 developed as its model. When the alterations of Ae are from 0.18 x 10 μm2 , 0.12 x 10 μm2 and 0.09 x 10 μm2 , at the same time the fraction mole (x) is raised twice, it makes positive relation to RB and β parameter, but negative relation to RC, fT, and fmax parameter. A model of HBT SiGe with x: 0.1 and Ae: 0.18 x 10 μm2 produces 0.57dB of Fn minimum, the value is less than the other of which has 0.64dB for Ae: 0.12 x 10 μm2 and 0.69 dB for Ae: 0.09 x 10. Then if fraction mole(x) is reduced for 50%, it causes nonlinear Fn raising which are 77%, 79% and 89% from the previous value. Noise figure (Fn) had a negative relationship with emitter stripe area (Ae), whereas the mole fraction (x) has a positive relationship; so the noise figure (Fn) can be made low by minimizing emitter stripe area (Ae) and raise the mole fraction (x).